PENGARUH STRATEGI PEMBELAJARAN AKTIF TIPE COLLEGE BALL TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII MTsN MODEL PADANG - Anjelina, Wira; Delsi K, Delsi K; Melisa, Melisa (Pendidikan Matematika, 2014)
ABSTRACTThis research is motivatedby thelow yieldsof mathematicallearning in class VIII MTsN ModelPadang2013/2014. This problem isthought to be dueto thestudentsunderstanding ofthe concept ofmathematicalsubject matteris stilllacking, the studenthas notmastered the subject matterandalsothe students responsibilitytotasksandexercisesthatthe teacheris stilllacking, soa lot ofstudentswhodo notdo the exercise. This studyaims to determinewhetherstudents understanding of mathematicalconceptsby implementinga strategyCollegeBallbetter than thestudentsunderstanding ofmathematicalconceptsby applyingconventional learning in class VIII students of MTsN ModelPadang. This type of researchisexperimentalresearch which used random research design toward the subject . The instrument usedin this studyisa testof understandingof mathematicalconcepts.. The data analysis techniqueusedisthe t test by MINITAB. Basedon the data analysiswithMinitab, noting that the twoclassesare normally distributedandhomogeneous.Hypotesis test result obtained P-value = 0.000meansless thanÎ±=0.05, then the hypothesis of research is received.It can be concludedthat thestudents understanding of mathematicalconceptsthatapply CollegeBall strategybetterthanthestudentsunderstanding ofmathematicalconceptsby applyingconventional learningonstudentsclass VIIIMTsNModelPadang